STEM literacy in growing vocational school student HOTS in science learning: A meta-analysis - Qori Agussuryani; Sudarmin Sudarmin; Woro Sumarni; Edy Cahyono; Ellianawati Ellianawati (International Journal of Evaluation and Research in Education (IJERE), 2022)
The low higher order thinking skills (HOTS) of vocational students is shown from the approaches and models used in learning that are not specific, learning activities are limited to methods that have not been able to grow HOTS. One of the approaches offered in science, technology, engineering, and mathematics (STEM). The research objective was to analyze STEM in growing HOTS through literature studies. The data collection method used a STEM systematic review from 2016-2020 based on the indexed findings of Google Scholar and Scopus (Database: Elsevier, Scopus, and Science Direct). Qualitative descriptive data analysis technique was employed on inductive deductive patterns. Based on data analysis, there are findings of 18 Google Scholar indexed articles and 20 Scopus indexed articles according to the inclusion criteria. The results showed that: i) STEM integration patterns in growing HOTS obtained six STEM literacy patterns of 28% on Google Scholar and four STEM integration patterns by 65% in Scopus; ii) The trend of STEM and HOTS research from 2016-2020 has increased the most in 2020 by 56% on Google Scholar and 40% on Scopus. Most of the methods used are research and development (R&D) with data analysis techniques in the form of t-test on Google Scholar data and survey methods with descriptive analysis on Scopus data. The difference in the publication trend on the integration pattern, the number of samples used is greater in the Scopus data. The method used is more dominant in the survey than R&D, but whatever the research design in STEM literacy is, in principle, it can empower HOTS to increase learning activities.